Analisa Pengaruh Current Ratio (CR), Debt to Equity Ratio (DER), Dan Return On Asset (ROA) Terhadap Harga Saham Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Tercatat Di Bursa Efek Indonesia (BEI) Periode 2018 -2022 - Dandono, Yustinus Rawi; Nabilah, Reihana (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
This research aims to determine the influence of the variables Current Ratio, Debt to Equity Ratio, and Return on Assets on stock prices. The method used in this research is multiple linear regression involving classical assumption tests, and continuing partial tests and simultaneous tests.From the third variable, it is explained that the CR and ROA variables have a significant influence on share prices. The DER variable does not have a significant influence on stock prices. And the predictive ability of the third independent variable on Stock Prices obtained by Adjusted R Square is 53.5% while the remaining 46.5% is influenced by other variables such as ROE, ROI, PER, PBV, NPM and inflation rate.